Geophysical study in a diesel contaminated area due to a railway accident in cerquilho (SP) - Moreira, César Augusto [UNESP]; Junqueira, Paula Gomes [UNESP]; Casagrande, Matheus Felipe Stanfoca [UNESP]; Targa, Débora Andrade [UNESP] (Sociedade Brasileira de Geofisica, 2019)
In São Paulo State, there are hundreds of contaminated areas due to leakage of hydrocarbons in gas stations, industry or transportation. Chemical compounds transportation is a high-risk activity in function of the unpredictability of accidents. The integration between geophysical data and soil/groundwater chemical analyzes provides a comprehensive and appropriate view to the management and monitoring of contaminated areas. This paper brings a set of geochemical data and geophysical diagnosis acquired in a diesel-contaminated area due to a railroad accident in 2002, during the transport of fuels in Cerquilho, São Paulo State. Furthermore, the site was still affected by the contamination when the geophysical acquisition was performed. DC Resistivity and Induced Polarization were performed, using electrical tomography technique. High chargeability values (2.97 mV/V) were associated with the neoformation of sulfides and hydroxides minerals in the unsaturated zone due to hydrocarbon degradation. Furthermore, the resistivity data indicated the presence of residual phase in the unsaturated zone by a heterogeneous pattern of anomalies. In addition, low resistivity values (<12 Ω.m) in the saturated zone indicated a dissolved phase of the contaminant. The geophysical diagnosis of residual phases in hydrocarbon contamination are used as a subsidy to the proper planning of remediation techniques in aquifer systems.
Keywords: DC resistivity; Hydrocarbon; Induced polarization; Leakage; Remediation; Residual phase